Incluir en el código de la niñez y adolescencia la determinación de criterio, para valorar la opinión de las/os adolescentes mayores de 14 años, cuando se trate de precautelar sus bienes - Lema Simbaña, Wilber Patricio (2016)
This research is based on one of the basic principles of constitutional law, the right to liberty, the same one that gives all and all Ecuadorians without exception, exercise their right to property in each and every one of the forms provided that these are framed and fulfill a role of social interest, which will be practiced responsibly. The owner of the property, safeguarding their social role at the time that this satisfies their personal and priority needs, then why our Civil Code establishes the form and have to exercise that right, but the Code of Childhood and Adolescence does not set that adolescents over 14 years, being immersed in a priority group freely exercise this right, so that only after hearing the opinion of the or adolescent judge value and is satisfied so that you can choose which parent and / or a third nearest administered their property, in order to ensure good living, their overall development as a human being. The statement is considered under the or adolescent in a time of emergency can benefit and meet their priority needs, being able to use the fruits and revenues they produce goods that are its property and are being misused by the person who is managing. Besides the free disposition of the fruits that come from their assets, currently is limited to what regulates the Civil Code, as this carries over resulting process it legally, but even when needs are emerging, for that concidero reason that the opinion on the management of their assets should be mandatory to be noimbre who manage their property, and that person is complying fully with its obligation, ie the administration is the most suitable to the characteristics of the adolescents needs. To this effect, despite these legal gaps that exist I must emphasize that this research is linked to formulate possible solutions, as this should not stop the integral development of adolescents. Hence the need to include urgent reform to legally determine the criteria and the obligation to implement the views of the (old) and children (you) about teenagers that is the most suitable person to manage their property.